Не бивши кума, не пити пива: «кумівство», стратегії і практики вибору хрещених батьків у суспільстві Гетьманщини - Сердюк, І. (Сiверянський лiтопис, 2017)
У статті досліджуються стратегії і практики вибору хрещених батьків у
суспільстві Гетьманщини. Розглядається два основних аспекти проблеми. Першим із
них є канонічна модель хрещення та її дотримання чи порушення. У ХVІІІ ст. церква
намагалася дисциплінувати священиків і паству та офіційно забороняла мати більше
одного хрещеного батька чи матері. Однак ці заборони послідовно ігнорувалися. Причини
цього пов’язані із другим аспектом – ставленням населення до ролі хрещеного батька
(матері) та відповідних зв’язків, котрі встановлювалися цим актом. В статье исследуются стратегии и практики выбора крестных родителей в обществе Гетманщины. Рассматривается два основных аспекта проблемы. Первым
из них является каноническая модель крещения и ее соблюдения или нарушения. В
XVIII в. церковь пыталась дисциплинировать священников и паству и официально
запрещала иметь более одного крестного отца или матери. Однако эти запреты последовательно игнорировались. Причины этого связаны со вторым аспектом – отношением населения к роли крестного отца (матери) и соответствующих связей, которые устанавливались этим актом. The article examines the strategies and practices of choosing baptized parents in society of
Hetmanschyna. Two main aspects of the problem are considered. The first of these is the canonical
model of baptism and its observance or violation. In the XVIII century. the church tried to
discipline the priests and the flock and officially forbade having more than one godfather or
mother. However, these prohibitions were consistently ignored. The reasons for this are related
to the second aspect – the attitude of the population towards the role of the godfather (mother)
and the relevant ties that were established by this act. The contemporary society considered
participating in the baptism of the child as an opportunity to establish new connections that
could not be made through marriage. Given that coercion was seen as a blood affinity, it gave
reason to hope for protection, help. These expectations regarding the child served as a kind of
fuse in the case of orphans. Parents could also take advantage of new ties to implement their
own life strategies.